Simulations of Southern Hemisphere warming and Antarctic sea-ice changes using global climate models - Wu, X; Budd, WF; Jacka, J (1999)
A combination of modelling techniques is used in conjunction with the limited available observational data to examine Antarctic sea-ice changes with global warming over the past century. Firstly, a coupled global climate model is forced by prescribing the effect of increasing greenhouse gases from last century to the present. Secondly, the GISST (U.K. Meteorological Office global sea-ice and sea surface temperature) observational dataset is used to force an atmosphere–sea-ice model to compute changes in the Antarctic sea ice from last century to the present. Thirdly, the global sea-surface-temperature (SST) anomalies derived from the coupled model are used to force the atmosphere–sea-ice model over the same period. The change in the Southern Hemisphere annual mean surface temperature simulated by the coupled model with greenhouse-gas forcing is about 0.6°C, which is similar to the observed change. Over the Antarctic (poleward of 60° S) the corresponding simulated change is about 0.7°C, which also appears compatible with observations. The reduction in summer sea-ice extent simulated by the CSIRO (Commonwealth Scientific and Industrial Research Organisation) coupled model is 0.44° lat. which is, in general, less than the observed change. For the two SST forcing cases the changes are, in general, larger than indicated by the observations. It is concluded that future changes of reduced sea-ice extent from increasing greenhouse gases as simulated by the CSIRO coupled model are not expected to be overestimates.